A Study of the Adsorption of Pb(II) and Cu(II) by Cross Linked Chitosan - Hồ , Thị Yêu Ly (Journal of Technical Education Science, 2010)
The adsorption of Pb(II) and Cu(II) by cross linked chitosan was conducted by the batch mode. At pH 6 and contact time 120 and 180 min for Pb(II) and Cu(II), respectively, the maximum percentage adsorption was reached for both ions. The effect of ion NO3- on the adsorption of Pb(II )and Cu(II) was investigaed. The results showed that in the presence of NO3-, the adsorption capacity of both ions was increased. For the adsorption isotherm studies, the Langmuir and Freundlich models were used. The constants of two models with correction coefficients r2 were obtained. The results indicated that the adsorption isotherm of Pb(II) and Cu(II) by cross linked chitosan at given conditions was followed both the Langmuir and Fruendlich models. From the Langmuir model, the maximum adsorption capacity of cross linked chitosan for Pb(II) and Cu(II) were obtained 13.8 and 5.5 mg/g, respectively. From the results obtained, it could be concluded that cross linked chitosan can be used for enrichment of Pb(II) and Cu(II) from aqueous solution.